Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/biomedicines11040993
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and Clinical Verification of the Blood Co-Expression Genes of Type 2 Diabetes Mellitus and Mild Cognitive Dysfunction in the Elderly

Abstract: With the development of society, the incidence of dementia and type 2 diabetes (T2DM) in the elderly has been increasing. Although the correlation between T2DM and mild cognitive impairment (MCI) has been confirmed in the previous literature, the interaction mechanism remains to be clarified. To explore the co-pathogenic genes in the blood of MCI and T2DM patients, clarify the correlation between T2DM and MCI, achieve the purpose of early disease prediction, and provide new ideas for the prevention and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“… 40 Zhang et al reported that ALDH2 is one of the co-pathogenic genes of T2DM and mild cognitive impairment (MCI). 41 Another study reported that the ALDH2 polymorphism might association with susceptibility to DM and showed a significantly lower risk of T2DM for ALDH2 G/G and G/A genotypes in China. 42 Xu et al found that ALDH2 polymorphism is associated with an increased risk of T2DM in women with coronary artery disease (CAD).…”
Section: Discussionmentioning
confidence: 99%
“… 40 Zhang et al reported that ALDH2 is one of the co-pathogenic genes of T2DM and mild cognitive impairment (MCI). 41 Another study reported that the ALDH2 polymorphism might association with susceptibility to DM and showed a significantly lower risk of T2DM for ALDH2 G/G and G/A genotypes in China. 42 Xu et al found that ALDH2 polymorphism is associated with an increased risk of T2DM in women with coronary artery disease (CAD).…”
Section: Discussionmentioning
confidence: 99%
“…In women, the presence of estrogenic activity slows down the progression of Parkinson's disease, as the hormone gives these subjects high levels of physiological dopamine at the nigro-striatal level [101]. This suggests that estrogens may have a role in preventing the disease itself due to their anti-inflammatory activity, which counteracts the chronic inflammatory state induced by IR [102,103].…”
Section: Insulin Resistance and Cognitive And Neurological Diseasesmentioning
confidence: 99%